PERSONAL ACADEMIC AND ENVIRONMENTAL FACTORS AS DETERMINANTS OF PERCEIVED COMPLEXITY IN ACCOUNTING COURSES - Ulfa Nurhayani; Haryani Pratiwi Sitompul; Weny Nurwendary; Rini Herliani; Sondang Aida Silalahi; Nabila Tijani Tharifah (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
This study aims to examine the influence of personal, academic, and environmental factors on students’ perceived complexity of accounting courses. Accounting is frequently regarded as a difficult subject due to its abstract concepts, procedural rigor, and analytical demands, which often affect students’ motivation, engagement, and learning outcomes. Understanding the determinants of perceived complexity is essential for improving the effectiveness of accounting education. This research employed a mixed-method explanatory approach, in which quantitative data served as the primary source of analysis and qualitative data supported the interpretation of results. Quantitative data were collected through a survey of 260 Accounting Education students at Universitas Negeri Medan using a structured questionnaire measured on a five-point Likert scale. The sample was selected using proportionate stratified random sampling based on semester level. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. To strengthen the empirical findings, qualitative data were obtained through classroom observations and semi-structured interviews with selected students and lecturers. The results indicate that personal factors—including learning motivation, academic ability, prior learning experience, and attitudes toward accounting—significantly reduce students’ perceived complexity of accounting courses. Academic factors, such as curriculum structure, teaching methods, and instructional material quality, also play a significant role in facilitating understanding and reducing cognitive load. Furthermore, environmental factors, encompassing academic, social, and physical learning environments, positively influence students’ engagement and perceptions of accounting learning. Qualitative findings confirm that interactive teaching methods and supportive learning environments enhance students’ confidence in dealing with complex accounting material. This study contributes to accounting education literature by demonstrating that perceived course complexity is multidimensional and shaped by the interaction of internal and external factors. Practically, the findings suggest that educators and institutions should adopt student-centered teaching strategies, adaptive curricula, and supportive learning environments to mitigate perceived complexity and improve learning outcomes.  Key words: Personal factors, Academic factors, Environmental factors, Accounting complexity, Students’  perception